„Nie drażnić bestii”. Konsekwentny unik Soboru - GRAJEWSKI, Andrzej (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The Second Vatican Council provided a new concept of the presence of the Church in the contemporary world. However, despite the fact that the Council referred to most of the burning issues of the time, no reference to communism is present in any of its documents. The silence of the Council in this respect was all the more astonishing, because it was summoned exactly at the time when communism was the greatest challenge to the Church. There were a few reasons though why the Second Vatican Council decided not to take a formal position regarding the question of communism. According to the plans advanced by John XXIII, and subsequently by Paul VI, the agenda of the Council comprised taking positive steps, which excluded pronouncing new anathemas or issuing critical opinions. An important goal of the Council was starting a dialogue with other Christian Churches. Talks in this vein were continued, among others, with the Moscow Patriarchate represented by Metropolitan Nicodemus (Rotov). In August 1962, during Metropolitan Nicodemus’s meeting with Card. Eugène Tisserant, Dean of the Sacred College of Cardinals and former Prefect of the Congregation for the Oriental Churches, which took place in Metz, it was settled that observers representing the Moscow Patriarchate would be allowed to come to the Council provided no condemnation of communism was issued by the Council Fathers. The Metz agreement was treated as binding by John XXIII and later by Paul VI, which had its impact on the course of the Conciliar debates. Both Popes, as well as numerous influential hierarchs, were convinced that promulgation of a document including a condemnation of communism would restrict the Holy See’s capability of negotiations. Instead of making a radical gesture, they chose to put the hope for improvement of the fate of the Christians behind the iron curtain in a policy of agreements and settlements with particular communist states. The absence of a condemnation of communism in the Council’s documents was then a deliberate evasion in the face of the overt demand to take a clear stand regarding this issue expressed by numerous participating Bishops. The entire issue affected not only the course of the Conciliar debates, but also the subsequent reception of the Council’s accomplishments, which contributed to divisions within the Church. Translated by Dorota Chabrajska